Resource Remobilization Efficiency Varies With Plant Growth Form but Not Between Fens and Bogs - Cong, Yu; Zhang, Zhongsheng; Liu, Bo; Chen, Yingyi; Li, Xiao; Jiang, Ming; Li, Mai-He (Frontiers in Earth Science, 2022)
Resource resorption from senescing leaves is an important strategy for internal nutrient recycling in plants. However, our understanding of whether the responses of resource remobilization to mire types (fens vs. bogs) differ among various plant growth forms remains unclear. We thus assessed resource remobilization among various growth forms in fens and bogs in the Hani peatland in the Changbai Mountains, northeastern China. We analyzed and compared the concentrations of non-structural carbohydrates (NSCs), nitrogen (N), phosphorus (P), and potassium (K) in leaves and roots collected in August (mid-season) and September (end-season), and calculated the resource remobilization efficiency (RRE) of four species belonging to four growth forms grown in both fens and bogs. The deciduous dwarf trees (Betula fruticosa) and perennial grass (Phragmites australis) had relative higher leaf RRE than the moss (Sphagnum magellanicum). Although leaf nutrient RRE did not differ between fens and bogs, the deciduous dwarf trees had a higher leaf NSC RRE in bogs than in fens, and the moss NSC RRE was lower in bogs than in fens. Our results suggest that reallocation of mobile carbohydrates seems to be more sensitive to the growth condition than nutrients (N, P, and K) under nutrient-poor inhabits, which may be one of the reasons leading to nutrient limitation in peatlands.